Examination of the heavy metal uptake of carrot (daucus carota) in different soil types - Szabó, György; Czellér, Krisztina (Acta Geographica Debrecina Landscape & Environment series, 2009)
In this paper the heavy metal uptake of carrot (Daucus carota) is studied in sample areas with different soil types. Our aim is to examine how the different soil types possessing different characteristics affect the heavy metal uptake and distribution in the plant. Correlation analyses were carried out in order to determine which of the total heavy metal concentrations and soil characteristics (pH, CaCO3-content, humus content, granulometric composition) play the most important role in the uptake of the Co, Cu, Fe, Ni, Mn, Zn and in the metal distribution in the examined plant. Soil and plant samples were collected from 5 different Hungarian areas in July, 2008. In the cases of soils with different soil characteristics, the examined plants are supposed to give varied physiological responses. During the examination we proved that the genetic type and the heavy metal content of the soil do not significantly affect the heavy metal uptake of carrot. The granulometric composition of the soil has the most considerable effect but this factor only affects the rate of the metal uptake in 50% of the examined heavy metals (Ni, Mn, Zn).